1985
DOI: 10.1007/bf02372225
|View full text |Cite
|
Sign up to set email alerts
|

Interference and competitive behaviour of the aphid predators,Chrysoperla carnea andCoccinella septempunctata in the laboratory

Abstract: Interference and competition between Chrysoperla carnea (Stephens) and Coccinella septempunctata L. was investigated in the absence and presence of aphid prey. When larvae of similar vigour encountered each other, C. carnea larvae were superior to C. septempunctata. Otherwise the larger of 2 individuals always killed the smaller. In the absence of prey C. carnea adults were attacked by their own 2nd and 3rd instar larvae as well as by 3rd instar larvae of C. septempunctata. In all encounters the adults of C. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 12 publications
(5 reference statements)
3
39
0
1
Order By: Relevance
“…Reduced food intake by preimaginal stages of predatory arthropods generally has been shown to result in reduced survival, increased developmental time, and reduced adult weight and reproduction (Smith 1965b;Turnbull 1965;Canard et al 1984;Sengonca and Frings 1985;Valicente and O'Neil 1995;Hodek and Honek 1996). For example, Legaspi and O'Neil (1994) demonstrated that nymphs of Podisus maculiventris (Say) (Heteroptera: Pentatomidae) fed a minimal diet had lower survival, longer developmental time, and developed into smaller adults than well-fed nymphs.…”
Section: Discussionmentioning
confidence: 94%
“…Reduced food intake by preimaginal stages of predatory arthropods generally has been shown to result in reduced survival, increased developmental time, and reduced adult weight and reproduction (Smith 1965b;Turnbull 1965;Canard et al 1984;Sengonca and Frings 1985;Valicente and O'Neil 1995;Hodek and Honek 1996). For example, Legaspi and O'Neil (1994) demonstrated that nymphs of Podisus maculiventris (Say) (Heteroptera: Pentatomidae) fed a minimal diet had lower survival, longer developmental time, and developed into smaller adults than well-fed nymphs.…”
Section: Discussionmentioning
confidence: 94%
“…In the pupae, the dense hair cover acts as a protection against ants. The main threats to coccinellid larvae may come from species that exploit the same resources, such as heterospecific coccinellids (Agarwala and Dixon, 1992;Obrycki et al, 1998), syrphids (Hindayana et al, 2001), chrysopids (Sengonca and Frings, 1985;Lucas et al, 1998;Phoofolo and Obrycki, 1998), and pentatomids (Mallampalli et al, 2002;De Clercq et al, 2003). However, little predation has been directly observed toward H. axyridis larvae except by coccinellid larvae Ware and Majerus, 2008) or by the pentatomid bug Podisus maculiventris (Say) (De Clercq et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to classical predation, the organisms involved in IGP do not always have well defined roles; the same organism may be either predator or prey, depending on a variety of factors (Polis et al, 1989). The outcomes of such interactions are usually influenced by the relative size, mobility and density of the organisms, as well as by their feeding specificity and morphology, and by the densities of extraguild prey (Sengonca and Frings, 1985;Polis et al, 1989;Lucas et al, 1998;Hindayana et al, 2001;Lucas, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…According to the classic rule of size (Sengonca and Frings, 1985;Lucas et al, 1998;Hindayana et al, 2001;Sato et al, 2003), it is predicted that the larger syrphid larvae should mostly act as the intraguild predators, while the smaller mirid should serve as the intraguild prey.…”
Section: Introductionmentioning
confidence: 99%